Community Archiving Independent Media - Jimenez, Mona (KULA)

(untitled) (University of Victoria Libraries, 2018)
Collections of independent, non-commercial works often represent voices and speak to topics not seen in mainstream media, and they are still often cared for outside of major collecting institutions. Since 2011, activist audiovisual archivists have organized Community Archiving Workshops (CAWs) in the US and beyond to help caretakers of endangered media and film collections jump-start preservation efforts. In the spirit of ‘each one, teach one,’ experienced archivists share skills with other volunteers to inspect and inventory a collection, thus giving caretakers the data they need to select priority works for preservation. CAW organizers are committed to training more people to carry out CAWs in their own communities; a grant-funded project will pilot this approach in partnership with cultural heritage organizations in three regional hubs (Nashville, TN; Madison, WI; and Oakland, CA) beginning in 2018.